The role of interviewer encounters in panel responses on life satisfaction - Adrian Chadi (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2013)
This paper examines a common explanation why participants of panel surveys may report declining life satisfaction over time. In line with the argument of developing trust relationships between interviewers and interviewees, the analysis reveals positive effects in reported life satisfaction when the person conducting the interview changes to an unfamiliar individual. Yet, the evidence also shows that the overall decline is determined by years in the panel, rather than by number of encounters with one specific interviewer. The realization that such response artifacts can affect the analysis of life satisfaction leads to some important conclusions.
Keywords: C8; I3; 330; Life satisfaction; panel effect; survey design; response bias; interviewer effects